Microbial Associations of Abyssal Gorgonians and Anemones (>4,000 m Depth) at the Clarion-Clipperton Fracture Zone - Elena Quintanilla; Clara F. Rodrigues; Isabel Henriques; Isabel Henriques; Ana Hilário (Frontiers in Microbiology, 2022)
Deep coral-dominated communities play paramount roles in benthic environments by increasing their complexity and biodiversity. Coral-associated microbes are crucial to maintain fitness and homeostasis at the holobiont level. However, deep-sea coral biology and their associated microbiomes remain largely understudied, and less from remote and abyssal environments such as those in the Clarion-Clipperton Fracture Zone (CCZ) in the tropical Northeast (NE) Pacific Ocean. Here, we study microbial-associated communities of abyssal gorgonian corals and anemones (>4,000 m depth) in the CCZ; an area harboring the largest known global reserve of polymetallic nodules that are commercially interesting for the deep-sea nodule mining. Coral samples (n = 25) belonged to Isididae and Primnoidae families, while anemones (n = 4) to Actinostolidae family. Significant differences in bacterial community compositions were obtained between these three families, despite sharing similar habitats. Anemones harbored bacterial microbiomes composed mainly of Hyphomicrobiaceae, Parvibaculales, and Pelagibius members. Core microbiomes of corals were mainly dominated by different Spongiibacteraceae and Terasakiellaceae bacterial members, depending on corals’ taxonomy. Moreover, the predicted functional profiling suggests that deep-sea corals harbor bacterial communities that allow obtaining additional energy due to the scarce availability of nutrients. This study presents the first report of microbiomes associated with abyssal gorgonians and anemones and will serve as baseline data and crucial insights to evaluate and provide guidance on the impacts of deep-sea mining on these key abyssal communities.